A RsrC-RsrA-RsrB transcriptional circuit positively regulates polysaccharide-degrading enzyme biosynthesis and development in Penicillium oxalicum - Yuan-Ni Ning; Xue Liang; Xin Shen; Di Tian; Wen-Tong Li; Xue-Mei Luo; Jia-Xun Feng; Shuai Zhao (Communications Biology, 2024)
Abstract Filamentous fungi produce polysaccharide-degrading enzymes, which is controlled by poorly understood transcriptional circuits. Here we show that a circuit comprising RsrC-RsrA-RsrB (Rsr: production of raw-starch-degrading enzyme regulator) that positively regulates production of raw starch-degrading enzymes in Penicillium oxalicum. Transcription factor (TF) RsrA is essential for biosynthesis of raw starch-degrading enzymes. RsrB and RsrC containing Zn2Cys6- and C2H2-zinc finger domains, act downstream and upstream of RsrA, respectively. RsrA activates rsrB transcription, and three nucleotides (G-286, G-287 and G-292) of rsrB promoter region are required for RsrA, in terms of TF, for binding. RsrB165−271 binds to DNA sequence 5’-TCGATCAGGCACGCC-3’ in the promoter region of the gene encoding key raw-starch-degrading enzyme PoxGA15A. RsrC specifically binds rsrA promoter, but not amylase genes, to positively regulate the expression of rsrA and the production of raw starch-degrading enzymes. These findings expand complex regulatory network of fungal raw starch-degrading enzyme biosynthesis.